A first study on the usability and feasibility of four subtypes of suicidality in emergency mental health care - Remco F. P. de Winter; Connie M. Meijer; Anne T. van den Bos; Nienke Kool-Goudzwaard; John H. Enterman; Manuela A.M.L Gemen; Chani Nuij; Mirjam C. Hazewinkel; Danielle Steentjes; Gabrielle E. van Son; Derek P. de Beurs; Marieke H. de Groot (BMC Psychiatry, 2023)
Abstract Background Based on clinical experience, a (hypothetical) four-type model of suicidality that differentiates between subtypes with a unique pathway to entrapment ((h)4ME)was developed. The subtypes are: 1) perceptual disintegration (PD), 2) primary depressive cognition (PDC), 3) psychosocial turmoil (PT) and 4) inadequate communication/coping (IC). This study was carried out to examine the usability and feasibility of the subtypes in an absolute and dimensional way with the SUICIDI-2 instrument. Objective A first step was to examine the model and the SUICIDI-2 instrument for usability and feasibility in clinical practice. We aim to investigate the’real life’ practical application of the model and hope the feedback we get after practical use of the model will help us with improvements for the model and the SUICIDI-2 instrument. Methods Discharge letters to general practitioners of 25 cases of anonymized suicidal emergency patients were independently reviewed by three psychiatrists and three nurses. Using the SUICIDI-2 instrument, describing the proposed subtypes, cases were classified by the psychiatrists and nurses. Intraclass Correlation Coefficients (ICC) for absolute/discrete and dimensional ratings were calculated to examine the model’s usability and the instrument‘s feasibility. The study was approved by the ethical board. Results All raters were able to recognize and classify the cases in subtypes. We found an average measure of good reliability for absolute/(discrete) subtypes. For dimensional scores, we found excellent average measures for the subtype PDC, and good average measures for the subtypes PD, PT and IC. The reliability of dimensional score for the SUICIDI-2 was relatively lower than an alternative dimensional rating, but had good ICC values for all subtypes. After reviewing the results though, we found some inconsistently assessment between raters. This was ground to narrow down the criteria per subtype to describe the subtypes more precisely. This resulted in adjusted formulations for subtypes PD and IC and agreement was achieved about formulations in the revised SUICIDI-3. Conclusions The hypothetical model of entrapment leading to suicidality shows promising results for both the usability and feasibility of the SUICIDI instrument. Follow up studies with participants with a more diverse background may show consistency and validity for the model.